In Search of Atmospheres: Directions, Methods, Perspectives: An interview with Tonino Griffero - Sokolovskiy, Sergei (Anthropologica)

(untitled) (University of Victoria, 2024)
The interview touches upon the diversity of traditions (including national ones) of atmospheric research, on the correlation of the concepts of (affective) atmosphere with the concepts of mood (Stimmung) and ambiance, on research methods and ways of conceptualizing atmospheric phenomena by the German phenomenologist, Hermann Schmitz, and the specialist in aesthetics, Gernot Böhme, and, finally, on the prospects of using the methods and approaches under consideration in social sciences.